Detection, Chemical Analysis and Pharmacological Characterization of Dipyanone and other New Synthetic Opioids Related to Prescription Drugs - M.M. Vandeputte; S.E. Walton; S.A. Shuda; A.J. Krotulski; C.P. Stove (Emerging Trends in Drugs, Addictions, and Health)
Introduction: New synthetic opioids (NSOs) continue to emerge on recreational drug markets. We performed in vitro pharmacological characterization of dipyanone, desmethylmoramide and acetoxymethylketobemidone (O-AMKD) – recent NSOs that are structurally related to the prescription opioids methadone and ketobemidone. Dipyanone was also detected for the first time in a seized powder and quantified in a postmortem toxicology case. Methods: In the applied cell-based assay, activation of human MOR, fused to one subunit of a nanoluciferase, leads to recruitment of βarr2, fused to the complementing subunit. The resulting functional complementation enables restoration of luciferase activity (NanoBiT®, Promega). Quantification of dipyanone in blood was done via liquid chromatography tandem quadrupole mass spectrometry using standard addition. Results: Dipyanone (EC50=39.9 nM; Emax=155% vs. hydromorphone) is about equally active as methadone (EC50=50.3 nM; Emax=152%), whereas desmethylmoramide (EC50=1335 nM; Emax=126%) is considerably less active. A close structural analogue of ketobemidone (EC50=134 nM; Emax=156%), O-AMKD showed a lower potency (EC50=1262 nM) and efficacy (Emax=109%). Furthermore, dipyanone was quantified in blood (370 ng/mL) and detected alongside other NSOs and novel benzodiazepines. Conclusions: The uncontrolled availability and unsupervised use of NSOs are reasons for concern. Careful monitoring is required to detect other NSOs related to prescription opioids that may emerge on recreational drug markets.